MENUJU DESA SEHAT HILINAMAZIHONO MELALUI GENCATA (GERAKAN CEGAH STUNTING) KECAMATAN O’O’U NIAS SELATAN TAHUN 2024 - Famea Satulo Dakhi; Aprilianus Ndruru; Rehati Ndruru; Lisda Putri Wati Telaumbanua; Ica Anjeli Daeli; Renungkan Gaho; Aloysius Boby Halawa; Rekalaila Demerni Halawa; Sesilia Nelsia Yeslina Duha; Vinsensius Sofunatola Buulolo; Animan Lature; Edar Sintasi Maduwu; et al. (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of this community service is to implement the GENCATA Program (Movement to Prevent Stunting), which was initiated to raise awareness and knowledge among the community about stunting prevention through the empowerment of village community groups, intensive socialization regarding stunting, local food management, and waste management practices. This program involves the formation of a Sustainable Community Care Group for Stunting, educational programs about stunting, and intensive stunting awareness campaigns by stunting care groups. It also focuses on women’s empowerment through balanced nutrition practices, healthy eating habits, and hygiene at home, along with the "Healthy Kitchen to Combat Stunting" (DASHAT) initiative to utilize local food and promote hygiene practices and waste management. The results indicate an increase in community understanding of the importance of balanced nutrition and hygiene practices, the establishment of active stunting care groups, and an improvement in village communities’ skills in preventing stunting, managing waste, and implementing DASHAT activities for local food management. This has enabled them to independently practice healthy eating and hygiene at home. Gradually and sustainably, this program is expected to improve nutritional status among children and pregnant women. The program has proven effective in creating positive changes, although ongoing support and innovation are still needed to strengthen the results achieved.